IMPLEMENTASI AGAMA DALAM MEWUJUDKAN KELUARGA SAKINAH - Enung Asmaya (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2012)
continuously apply Islamic values as a foundation in pursuing the family life. Thisfoundation functions as a guidance and direction for them to solve the problems of life sothat peaceful (sakinah) family can be achieved.When religious values are well implemented in the family life, the followingconditions will be attained: every family member will have a sense of affection, be closedto, have no prejudice, trust, regard, and advise one another, as well as apply problemoriented perspective in playing their roles and functions in the family